Efficacy and Tolerability of CyberKnife Stereotactic Robotic Radiotherapy for Primary or Secondary Orbital Lesions: A Single-Center Retrospective Experience. (19th July 2019) - Desideri, Isacco; Francolini, Giulio; Carta, Giulio Alberto; Di Cataldo, Vanessa; Masi, Laura; Meattini, Icro; Bonomo, Pierluigi; Loi, Mauro; Greto, Daniela; Visani, Luca; Lo Russo, Monica; Grassi, Roberta; et al.
Introduction: Orbital lesions are rare, but are likely to become symptomatic and can impact on patients' quality of life. Local control is often difficult to obtain, because of proximity to critical structures. CyberKnife stereotactic robotic radiotherapy could represent a viable treatment option. Materials and Methods: Data on patients treated for intraorbital lesions from solid malignancies were retrospectively collected. All patients underwent treatment with CyberKnife system. We analyzed local control, response rate, symptoms control, progression-free survival and overall survival, acute and late toxicity. Results: From January 2012 to May 2017, 20 treatments on 19 patients were performed, with dose ranging from 24 to 35 Gy in 1 to 5 fractions, prescribed at an average isodose line of 79.5% (range: 78-81). After a mean follow-up of 14.26 months (range: 0-58), overall response rate was 75%, with 2 and 4 patients presenting a partial and complete response, respectively. Mean time to best measured response was 15.16 months (range: 2-58). Thirteen patients were alive, with a local control rate of 79%. Mean time to local progression was 5 months (range: 3-7). Three patients reported improvement in symptoms after treatment. Mean planning target volume dose coverage was 97.2% (range: 93.5-99.7). Mean maximum dose (D max) to eye globe, optic nerve, optic chiasm, and lens was 2380.8 cGy (range: 290-3921), 1982.82 cGy (range: 777.3-2897.8), 713.14 cGy (range: 219.5-2273), and 867.9 cGy (range: 38-3118.5). Four patients presented acute toxicity. Conclusion: This current retrospective series demonstrated that CyberKnife robotic stereotactic radiotherapy is a feasible and tolerable approach for intraorbital lesions.